Chemical control of white rust of mustard through seed treatment-cum-sprayand their economics - L.P. BHARGAVA and A NAG*, AK. BHARGA VA, A.K. SOBTI (Indian Phytopathology, 2002)
Field experiments were conducted during rabi 1991-93 and 1995-96 at the Agricultural Research Station, Dugrapura, Jaipur, India, to investigate suitable economically viable control measures for white rust (caused by Albugo candida) of Indian mustard(Brassica juncea). Seeds of the susceptible cultivar Varuna were treated with mancozeb or metalaxyl and the mustard plants were sprayed with mancozeb, mancozeb + metalaxyl or chlorothalonil once, twice or three times after sowing. All the treatments significantly reduced leaf infection. Seed treatment with metalaxyl was more effective than with mancozeb. Minimum disease intensity (16.8phi) was observed when mustard seeds were treated with metalaxyl and sprayed with chlorothalonil at 20, 40 and 60 days after sowing (DAS) or by seed treatment followed by 3 late sprays of mancozeb at 45, 60 and 75 DAS. These treatments also increased the yield significantly and were therefore the most economical.